2011
DOI: 10.2105/ajph.2010.300079
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Use of Indoor Tanning: A Large-Scale Evaluation of Psychosocial, Environmental, and Policy-Level Correlates

Abstract: Objectives We evaluated psychosocial, built-environmental, and policy-related correlates of adolescents’ indoor tanning use. Methods We developed 5 discrete data sets in the 100 most populous US cities, based on interviews of 6125 adolescents (aged 14–17 years) and their parents, analysis of state indoor tanning laws, interviews with enforcement experts, computed density of tanning facilities, and evaluations of these 3399 facilities’ practices regarding access by youths. After univariate analyses, we constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 35 publications
(44 reference statements)
6
82
1
2
Order By: Relevance
“…In addition to age and gender differences, adolescents with a more positive attitude toward tanning or tanned skin are more likely to use indoor tanning devices. [30][31][32][33][34][35][36][37][38][39] Perceived social norms regarding tanning and tanned skin (e.g., reporting that one's friends are tan or use indoor tanning devices) are also associated with indoor tanning among adolescents. 30,32,35,36,38 Indoor tanning is associated with other risky behaviors as well, such as alcohol, tobacco, and recreational drug use; poor sun protection behaviors; and unhealthy eating behaviors (such as dieting frequently to lose weight or using laxatives and vomiting to control weight).…”
Section: Correlates Of Indoor Tanningmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to age and gender differences, adolescents with a more positive attitude toward tanning or tanned skin are more likely to use indoor tanning devices. [30][31][32][33][34][35][36][37][38][39] Perceived social norms regarding tanning and tanned skin (e.g., reporting that one's friends are tan or use indoor tanning devices) are also associated with indoor tanning among adolescents. 30,32,35,36,38 Indoor tanning is associated with other risky behaviors as well, such as alcohol, tobacco, and recreational drug use; poor sun protection behaviors; and unhealthy eating behaviors (such as dieting frequently to lose weight or using laxatives and vomiting to control weight).…”
Section: Correlates Of Indoor Tanningmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39] Perceived social norms regarding tanning and tanned skin (e.g., reporting that one's friends are tan or use indoor tanning devices) are also associated with indoor tanning among adolescents. 30,32,35,36,38 Indoor tanning is associated with other risky behaviors as well, such as alcohol, tobacco, and recreational drug use; poor sun protection behaviors; and unhealthy eating behaviors (such as dieting frequently to lose weight or using laxatives and vomiting to control weight). 32,34,38,39 One large study 39 found adolescents who had a college-educated mother were less likely to tan, and female adolescents who participated in physical activity were less likely to tan than peers who did not.…”
Section: Correlates Of Indoor Tanningmentioning
confidence: 99%
See 3 more Smart Citations